Pengaruh Kualitas Produk Sayuran Organik Terhadap Kepuasan Konsumen dalam Membentuk Loyalitas Pelanggan (The Effect of Organic Vegetable Product Quality to Customer Satisfaction in Creating Customer Loyalty) - Nurul Hidayati; Ma'mun Sarma; Muhammad Syamsun (IPB University, 2014)
Development of organic vegetables in Bogor is still having problems. One is the failure to maintain market confidence. Failure is reflected in the behavior of consumers who are reluctant to buy organic product prevent consumers to buy back the organic products. This shows people confidence to attributes and benefits of organic products (organic vegetables) are not able to meet theor needs and create satisfaction in the minds of consumers so that customer loyalty can be realized. This study aimed to asses the effect of organic vegetable product quality to customer satisfaction and customer loyalty, and customer satisfaction to customer loyalty in Bogor city. The results of this study indicate that the quality of organic vegetable products directly gives positive and significant effect to customer satisfaction, customer satisfaction directly gives positive and significant effect to customer loyalty; and the quality of organic vegetable product through customer satisfaction indirectly gives positive and significant effect to customer loyalty. The quality of the product directly gives positive effect to customer loyalty, but it's not significant.Keywords : customer loyalty customer satisfaction, organic vegetables, product quality, Structural Equation Modeling